2008
DOI: 10.1016/j.ejheart.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Poor outcome in end‐stage heart failure patients with low circulating calcitriol levels

Abstract: Background: Vitamin D receptor knockout mice develop typical signs of congestive heart failure (CHF). In approximately 20% of stable CHF patients, frankly low concentrations of the vitamin D hormone calcitriol are found. Aims: We investigated whether serum calcitriol concentrations predict clinical outcome in end-stage CHF. Methods and results:We collected blood samples in 383 end-stage CHF patients who were on a waiting list for cardiac transplantation. We assessed associations of calcitriol with disease seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 36 publications
5
86
2
3
Order By: Relevance
“…The absence of vitamin D-mediated signal transduction and genomic activation reportedly results in cardiomyocyte overstimulation and increased contractility, which ultimately lead to cardiomyocyte hypertrophy (39,40). In fact, low serum 1,25D concentrations have been implicated in poorer clinical outcomes for end-stage chronic heart failure patients (41). Furthermore, low levels of 25D have been associated with heart failure and sudden cardiac death in the general population (40,42 GF, goodness-of-fit; DM, diabetes mellitus; CT, computed tomography; PWV, pulse wave velocity.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of vitamin D-mediated signal transduction and genomic activation reportedly results in cardiomyocyte overstimulation and increased contractility, which ultimately lead to cardiomyocyte hypertrophy (39,40). In fact, low serum 1,25D concentrations have been implicated in poorer clinical outcomes for end-stage chronic heart failure patients (41). Furthermore, low levels of 25D have been associated with heart failure and sudden cardiac death in the general population (40,42 GF, goodness-of-fit; DM, diabetes mellitus; CT, computed tomography; PWV, pulse wave velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Among 3299 patients referred for coronary angiography, low 25(OH)D as well as low 1,25(OH)2D levels were prospectively and independent of cardiovascular risk factors associated with an increased risk of death due to heart failure and of sudden cardiac death [86]. Furthermore, low 1,25(OH)2D concentrations were associated with increased mortality in 510 patients from a specialized heart center and were an independent predictor of death and the need for cardiac transplantation in 383 endstage congestive heart-failure patients [91,92]. In addition, low calcitriol levels were also associated with increased 1-year mortality in 171 cardiac transplant recipients [93].…”
Section: Vitamin D Deficiency and Heart Failure In Adultsmentioning
confidence: 99%
“…There are various opinions regarding the vitamin D level that leads especially to cardiovascular diseases. In a study performed by Cigolini et al (11) while this level was accepted as 20 ng/mL, in the study of Zittermann (12), this level was reported as 10 ng/ mL. While the deficiency limit was accepted as 15 ng/mL in the 2008 guideline of the Lawson Wilkins Pediatric Endocrine Association, we evaluated the patient groups by dividing them into 3 different groups: Those in whom the vitamin Table I.…”
Section: Discussionmentioning
confidence: 99%